Highly conserved repetitive DNA sequences are present at human centromeres. - Grady, D L (1992)
Highly conserved repetitive DNA sequence clones, largely consisting of (GGAAT)n repeats, have been isolated from a human recombinant repetitive DNA library by high-stringency hybridization with rodent repetitive DNA. This sequence, the predominant repetitive sequence in human satellites II and III, is similar to the essential core DNA of the Saccharomyces cerevisiae centromere, centromere DNA element (CDE) III. In situ hybridization to human telophase and Drosophila polytene chromosomes shows localization of the (GGAAT)n sequence to centromeric regions. Hyperchromicity studies indicate that the (GGAAT)n sequence exhibits unusual hydrogen bonding properties. The purine-rich strand alone has the same thermal stability as the duplex. Hyperchromicity studies of synthetic DNA variants indicate that all sequences with the composition (AATGN)n exhibit this unusual thermal stability. DNA-mobility-shift assays indicate that specific HeLa-cell nuclear proteins recognize this sequence with a relative affinity greater than 10(5). The extreme evolutionary conservation of this DNA sequence, its centromeric location, its unusual hydrogen bonding properties, its high affinity for specific nuclear proteins, and its similarity to functional centromeres isolated from yeast suggest that this sequence may be a component of the functional human centromere.